Attempted Criminal Acts and their Punishment by the Court - Hasani, Nikolin (Richtmann Publishing, 2012)
Even in our country there are made a number of offenses that remain tentative. The Penal Code implies that such works canbe classified likely every provided act, provided that â€œthe person takes direct action to do it, but not complete the act due to certaincircumstances indipendently from his willâ€. The most frequent subject of judicial review and penal punishment are the attempts dealingwith the murder or injury of a person and rarely for theft of physical property of someone else. Considerably, the attempts are providedas facts in the functional activity of civilians or in certain ranks of the hierarchy within the public administration. But in these areas thecrime is concealed. Except the cases that are caught by the High State Control, the audits usually consider them â€œadministrativeinfractionâ€, escaping from prosecution and judicial investigation by individuals who commit the attempts in this area. The focus of thisstudy is the analysis of some causes, the aspects of extension and the real punishment of â€œattemptsâ€.